Effect of Dietary Rumen Undegraded Protein (RUP) Level on Nutrient Intake and Digestion of Lactating Dairy Cows - Andriyani Astuti; Rochijan Rochijan; Budi Prasetyo Widyobroto (Buletin Peternakan, 2020)
The objective of this study was to examine the effect of different levels of rumen undegraded protein (RUP) in diets of lactating dairy cows on feed intake and nutrient digestion. The experiment was run according to completely randomized design with three treatments of complete feed rations containing different levels of rumen undegraded protein (RUP) and four replications for each treatment. In a digestibility trial, twelve Friesian Holstein cows were divided into three groups at each group consist of four cows and given three dietary treatments containing three levels of RUP, namely 7.43% of total crude protein /CP (P0), 8.49% of total CP (P1), and 9.45% of total CP (P2). Diets consisted of forages (King grass, Pennisetum hybrid) and concentrates at ratio of 50:50 in dry matter basis. The diets contained 18.25% CP and 61.75% total digestible nutrient (TDN). The cows fed diet (P0) were considered the control group. Drinking water was given ad libitum. This experiment was conducted for 21 days of adaptation period and seven days of collection period. In the collection period, samples of feed, refusal feed, and faecal were collected to get the chemical content includes dry matter (DM), organic matter (OM), ether extract (EE), crude fiber (CF), crude protein (CP), nitrogen-free extract (NFE) and total digestible nutrients (TDN). The data obtained were processed with one-way ANOVA (analysis of variance) and the difference existed between the means (P<0.05) would be analyzed with Duncan’s new multiple range test. The results showed that cows fed diet P2 (9.45% RUP in CP) in had significantly higher feed and nutrient intake (DM, OM, CP, CF, EE, TDN) and higher DM and OM digestibility compared to the other two treatments.